Records of Radio Aurora at Syowa Station, Antarctica in 1973 - ニシムタ, イチゾウ; ヤブウマ, ヒサシ; NISHIMUTA, Ichizo; YABUUMA, Hisashi (National Institute of Polar Research, 1975)
P(論文) departmental bulletin paper